Grain quality of the winter soft wheat varieties depending on the forecrops - O. A. Nekrasova; N. S. Kravchenko; N. G. Ignatieva; D. М. Marchenko; М. М. Ivanisov (Зерновое хозяйство России)
The purpose of the current work was to assess the grain quality indicators of the half-intensive types of winter soft wheat based on the forecrops of peas and maize for grain. The objects of research were 7 winter soft wheat varieties of half-intensive type “Don 107”, “Kapitan”, “Kaprizulya”, “Lilit”, “Krasa Dona”, “Ermak”, “Zhavoronok” developed in the FSBSI “Agricultural Research Center “Donskoy”. There has been established that the varieties grown after peas formed the grain nature weight and hardness at the level of the first quality class (according to the GOST requirements). The mass fraction of protein in the varieties “Kapitan”, “Kaprizulya” and “Ermak” corresponded to the second quality class (not less than 13.5%), and the rest of the samples belonged to the third class (not less than 12.0%). The amount of gluten in the grains of all varieties met the requirements for the third quality class (at least 23.0%). The samples “Kaprizulya” and “Zhavoronok” formed the largest amount, 25.6% and 25.7%, respectively. The falling number of all winter bread wheat varieties sown after peas and maize for grain corresponded to the standards of the first class (at least 200 s). Sown after maize for grain, the grain nature weight and hardness of the studied winter bread wheat varieties was at the level of the first quality class. The amount of protein in the grains of the most varieties met the requirements for the third quality class (at least 12.0%), except for the samples “Kaprizulya” (13.5%) and “Lilit” (13.5%), belonging to the second quality class. The amount of gluten of almost all samples met the GOST requirements for the forth quality class (not less than 18%), except for the variety “Zhavoronok”, whose grain corresponded to the third quality class (24.3%). There has been identified that peas was the best forecrop for obtaining winter bread wheat grain of half-intensive types at the level of I-III quality classes.